Children’s everyday lifeworlds out of school, in Hong Kong, Melbourne, and Singapore: Family, enrichment activities, and local communities - Nicola Yelland; Anita Kit-Wa Chan; Clare Bartholomaeus (Journal of Childhood, Education & Society)
Children’s everyday lives beyond school need to be considered holistically, in a way which moves beyond time use. In this article we draw on our adaptation of Sarah Pink’s (e.g. 2012) video re-enactment methodology for considering children’s out-of-school lifeworlds with Year 4 children (9 and 10 years old) in the global cities of Hong Kong, Melbourne, and Singapore. The data presented and discussed here was part of a larger Global Childhoods Project with children in the three global cities of Melbourne, Hong Kong, and Singapore. We use video re-enactment methodology to ‘think with’, to open up lines of inquiry and create conversations about children’s lives in and between the cities. Through these we consider the specifics of each city context, as well as socioeconomic and sociocultural contexts and factors that may impact differently on children’s everyday lifeworlds out-of-school within the same city. In order to focus the scope of the article, we consider family routines, enrichment activities and local communities, as aspects that we find useful to reflect on when exploring what children’s lives look like, in and across locations. We focus on these as we are interested in how they might add to the complexities of thinking about children in each location. We move between thinking about the re-enactments themselves and broader literature to explore children’s out-of-school lifeworlds in the three cities, painting a picture of children’s lives and considering the contexts which make particular activities and practices possible and desirable.